A finite element study of teeth restored with post and core: Effect of design, material, and ferrule - Viram Upadhyaya; Akshay Bhargava; Hari Parkash; B Chittaranjan; Vivek Kumar (Wolters Kluwer Medknow Publications, 2016)
Background: Different postdesigns and materials are available; however, no consensus exists regarding superiority for stress distribution. The aim of this study was to evaluate the effect of design and material of post with or without ferrule on stress distribution using finite element analysis. Materials and Methods: A total of 12 three-dimensional (3D) axisymmetric models of postretained central incisors were made: Six with ferrule design and six without it. Three of these six models had tapered posts, and three had parallel posts. The materials tested were titanium post with a composite resin core, nickel chromium cast post and core, and fiber reinforced composite (FRC) post with a composite resin core. The stress analysis was done using ANSYS software. The load of 100 N at an angle of 45΀ was applied 2 mm cervical to incisal edge on the palatal surface and results were analyzed using 3D von Mises criteria. Results: The highest amount of stress was in the cervical region. Overall, the stress in the tapered postsystem was more than the parallel one. FRC post and composite resin core recorded minimal stresses within the post but the stresses transmitted to cervical dentin were more as compared to other systems. Minimal stresses in cervical dentine were observed where the remaining coronal dentin was strengthen by ferrule. Conclusion: A rigid material with high modulus of elasticity for post and core system creates most uniform stress distribution pattern. Ferrule provides uniform distribution of stresses and decreases the cervical stresses.